1988
DOI: 10.1159/000167611
|View full text |Cite
|
Sign up to set email alerts
|

Role of an Intraperitoneal Catheter Implant in the Pathogenesis of Experimental Staphylococcus epidermidis Peritoneal Infection in Renal Failure Mice

Abstract: The influence of a permanent peritoneal catheter implant on the response of renal failure and control mice to peritoneal inoculation with 106 colony-forming units (CFU) Staphylococcus epidermidis was assessed 48 h after bacterial challenge. Two weeks after the surgical induction of renal failure or sham surgery, a segment of a peritoneal dialysis catheter was implanted entirely within the confines of the peritoneal cavity of mice. One month later peritoneal S. epidermidis inoculation was performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Another important difference to the model of El-Abbadi et al is the fact that our mice were not uremic and can thereby serve to study early changes in calcium and phosphorus metabolism in chronic kidney disease. Furthermore, we were able to evaluate the morphologic changes in the kidney due to high oral phosphate load, which is not possible in the renal ablation model of Gallimore et al 34 that is induced by sequential electrocoagulation of the right renal cortex and left nephrectomy. A limitation of our model is, in contrast to the typical histologic changes in humans with phosphate nephropathy, the lack of renal fibrosis in our db/db mice treated with the phosphorus-rich diet at the evaluated time point.…”
Section: Discussionmentioning
confidence: 99%
“…Another important difference to the model of El-Abbadi et al is the fact that our mice were not uremic and can thereby serve to study early changes in calcium and phosphorus metabolism in chronic kidney disease. Furthermore, we were able to evaluate the morphologic changes in the kidney due to high oral phosphate load, which is not possible in the renal ablation model of Gallimore et al 34 that is induced by sequential electrocoagulation of the right renal cortex and left nephrectomy. A limitation of our model is, in contrast to the typical histologic changes in humans with phosphate nephropathy, the lack of renal fibrosis in our db/db mice treated with the phosphorus-rich diet at the evaluated time point.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that the peritoneal catheter implant was a preferred site for bac terial persistence up to 48 h after 106 CFU IC S. epider midis inoculation and that bacterial clearance was fur ther compromised in renal failure mice [3]. In the cur rent study, most mice had cleared this inoculum 1 month after challenge; however, a small proportion of renal failure mice continued to harbor bacteria at the catheter site.…”
Section: Discussionmentioning
confidence: 96%
“…The surgical preparation and characteristics of this mouse model have been previously described [3,4,8], Placement of the catheter segment entirely within the confines of the peritoneal cavity preserved the integrity of intraperitoneal structures, and the resulting animal preparation was not limited by spontaneous sepsis con sequent to a catheter exit site through the abdominal wall and skin [8], At the time of our assessments, 7-10 weeks after surgery, renal failure mice were azotemic and presented significant anemia compared to sham-oper ated controls. Consistent with clinical observations dur ing chronic infections, sham-operated mice that were sacrificed at weekly intervals following 108 CFU IC 5. epidermidis inoculation developed significant anemia compared to infection-free controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations